2021
DOI: 10.3390/foods10092205
|View full text |Cite
|
Sign up to set email alerts
|

Variable Retort Temperature Profiles (VRTPs) and Retortable Pouches as Tools to Minimize Furan Formation in Thermally Processed Food

Abstract: Furan and its derivates are present in a wide range of thermally processed foods and are of significant concern in jarred baby and toddler foods. Furan formation is attributed to chemical reactions between a variety of precursors and a high processing temperature. Also, some kinetic models to represent its formation in different food materials have been studied and could predict the furan formation under simulated operating conditions. Therefore, this review aims to analyze and visualize how thermally processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…Shahidi and Oh ( 45 ) revealed that 2-pentyl-furan is oxidized by linoleic acid, which is an important factor leading to the formation of a peculiar smell in meat. In addition, 2-pentyl-furan has been listed as a substance that may cause cancer in humans ( 3 ). On the whole, the comprehensive aroma performance was in the order of microwave > stepwise retort > general retort.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shahidi and Oh ( 45 ) revealed that 2-pentyl-furan is oxidized by linoleic acid, which is an important factor leading to the formation of a peculiar smell in meat. In addition, 2-pentyl-furan has been listed as a substance that may cause cancer in humans ( 3 ). On the whole, the comprehensive aroma performance was in the order of microwave > stepwise retort > general retort.…”
Section: Resultsmentioning
confidence: 99%
“…A wireless temperature sensor (PICO VACQ; TMI-ORION, France) was used to monitor the temperature change at the cold point of the samples; the temperature change curves are shown in Figure 1C. The F 0 value of the samples were calculated using formula (1), and the F 0 values of the microwave, stepwise retort and general retort treatments all reached 3.0 min, which was regarded as achieving the same sterilization effect and commercial sterility (2)(3)(4). The parameters treated by microwave, stepwise retort and general retort are the corresponding parameters with F 0 value of 3.0 min obtained by many experiments.…”
Section: Thermal Lethality Curve and F 0 Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Mitigation measures for furan must consider sensory acceptability, nutrition, safety, including the possible formation of other food processing contaminants and economic benefits. To date, the principal proposed mitigation methods can be divided into three aspects: (i) removal or substitution of food ingredients (major furan precursors), (ii) addition of specific additives, especially some antioxidants, and (iii) changes in processing conditions or processing methods (Fardella et al., 2021; Kettlitz et al., 2019). Table 7 illustrates the recent mitigation measures for furan in different food systems, including the substitution of furan precursors, high‐pressure thermal sterilization (HPTS), employment of high hydrostatic pressure (HHP), ohmic heating, vacuum treatment, and addition of different antioxidants.…”
Section: Mitigation Measures Of Furan Exposurementioning
confidence: 99%
“…High-temperature and high-pressure sterilization can extend the shelf-life of cooked foods packed in retort pouches by 1 to 2 years, depending on the product [11,12]. Transglutaminase (TGs) enhances food texture by facilitating deamination, amine incorporation, and protein cross-linking [13].…”
Section: Introductionmentioning
confidence: 99%